Research Influence of Flux Air Gaps on Electromagetic Components of Shunt Reactors - Dung, Dang Chi; Bao, Doan Thanh; Nam, Phan Hoai; Tu, Pham Minh; Quoc, Vuong Dang (Engineering, Technology & Applied Science Research, 2024)
This paper introduces an evaluation of the flux air gaps of Shunt Reactors (SRs) to effectively mitigate fringing and leakage fluxes along the height of the iron core. The assessment of these discretely distributed flux air gaps in SRs is a rigorous and challenging process. To define their exact number, the case of one flux air gap is analyzed and investigated to observe/simulate the influence of the flux density distribution and the leakage flux along the air gaps on the reactive power and the operation conditions of the SR. Based on that, to reduce leakage flux, a large flux air gap is divided into smaller ones. Initially, an analytic model is presented to define the main parameters of the SRs. Then, a finite element method is developed to simulate electromagnetic quantities, such as the magnetic flux density, leakage flux, and electromagnetic force. The obtained results can help manufacturers define the exact number of flux air gaps along the iron core of the SR. From that, a suitable technology can be given in manufacturing high voltage SRs applied to high or super high voltage transmission lines.